Enhancing biodiversity and ecosystem services in quarry restoration – challenges, strategies, and practice. Issue 3 (23rd April 2020) - Salgueiro, Pedro A.; Prach, Karel; Branquinho, Cristina; Mira, António
Abstract : Although covering less than 1% of the land surface, extraction activities have long‐lasting impacts on local ecosystems, inevitably damaging biological diversity and depleting ecosystem services. Many extractive companies are now aware of their impacts and, while pressured by society, demand concrete solutions from researchers to reverse the effects of exploitation and restore biodiversity and ecosystems services. In this article, we compile and synthesize the contributions of the latest available research on quarry restoration. We depict and discuss some of the most pressing issues regarding (1) the challenges of restoring quarries; (2) the opportunities for biodiversity and ecosystem services delivery; and (3) outline further research addressing current gaps. We conclude that quarries pose different abiotic and biotic constraints that act interdependently, hampering the attainment of effective restoration if considered solely. Such constraints need to be addressed holistically to lastly encourage the self‐sustainability of the system by reinstating ecological processes. However, a restored site does not have to specifically mimic the pristine situation, as under certain conditions alternative approaches may uphold valuable natural assets contributing to the conservation of rare, restricted, or protected species and habitats.